Green urbanization efficiency of 18 urban agglomerations in China: Evidence from spatial–temporal evolution - Lv, Xiaofei; Wang, Lu (Frontiers in Earth Science, 2023)
As a highly developed spatial form of integrated cities, urban agglomeration has become an important fulcrum to promote economic development and regional growth. Its green urban efficiency is the key to achieve green growth. This study first proposes a slack-based measure model with undesirable output to evaluate green urbanization of 18 urban agglomerations in China. and integrated barycenter coordinate method, standard deviation ellipse, geographic detector model to analyze the spatial-temporal characteristics and its influencing factors of green urbanization efficiency in urban agglomerations. The main findings are as follows: (1)The green urbanization efficiency of urban agglomerations in China has shown the characteristics of “∧”, which rises first and then decreases. The spatial differentiation characteristics is not obvious and the gap is narrowing. (2)The center of green urbanization efficiency in China's urban agglomerations has always been located in the Central Plains urban agglomeration, with a small overall span and a relatively fixed position. The barycenter coordinates show a trend of shifting from east to north, but the transfer speed and rhythm are relatively slow. (3)The explanatory power of different influencing factors on spatial differentiation of green urbanization efficiency of urban agglomerations is different. The order of magnitude is urban population scale > investment growth > technology level > economic development > industrial structure.